Tellme Networks, Inc. - Isaacs, Andrew M.; Kinder, Shane; Osvald, John (London : SAGE Publications Ltd, 2017)
The Tellme Networks case study focuses on the company's future growth strategy in 2006. At the time, Angus Davis, co-founder of Tellme Networks was grappling with how to grow the company as Tellme reached an inflection point in its already successful business. The case study presents several growth options for students to consider, ranging from growing existing solutions to exploring international solutions. Each of these options would present unique challenges to the organization. The case study provides students with the opportunity to put themselves in Davis shoes and grapple with strategic and growth issues for the company.
Originally published in Isaacs, A. M., Kinder, S., & Osvald, J. (2006).Tellme Networks, Inc. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tellme Networks; Business planning -- Case studies; Strategic planning -- Case studies